A Review of the Use of Dogme ELT Method in Speaking Skills - Ali, Imanat; Zuraina, Ali; Ezihaslinda, Ngah (European Publisher, 2023)
English language skills have been taught through certain teaching methods as well as approaches. Dogme ELT method is one of the methods that can be regarded as an effective and result-oriented method for speaking skills. Speaking is an essential skill in all forms of communication. This is a review paper which presents the use of a recent ELT method, Dogme ELT for teaching language skills. The paper includes the analytical and critical discussion of using Dogme ELT, particularly for speaking skills. Additionally, it represents the learning attitudes of students toward Dogme ELT as well as the effectiveness of the method in classroom techniques. The paper adopted content analysis as the data analysis method. The contents of previous studies were analyzed; Dogme ELT and its effectiveness. Ten (10) articles were selected for analysis after screening the abstracts and the findings of the papers. The results depicted that Dogme ELT method is an effective method to improve EFL learners' speaking skills and to enhance classroom techniques which included students’ engagement in the lessons, discussions, interactions and rapport buildings in the ESL classroom.